E-Learning: Global Perspectives, Challenges and Educational Implications - Donnie, Adams; Kee-Man, Chuah (Nova Science Publishers, 2022)
As the world recovers from the unprecedented outbreak of the COVID-19 pandemic, the field of education continues to cushion the impacts of school closures and teaching disruption through various measures. E-learning, while not new, has taken a greater role in mitigating the effects of the pandemic. This book is not only a collection of chapters shared by researchers and academics but also a manifestation of the dedication of those involved in the pursuit of providing equitable and quality education through the support of e-learning tools and platforms.